2018
DOI: 10.3390/nu10101482
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Dietary Assessment in Youth with and Without Developmental Disabilities

Abstract: Obesity prevalence is higher in children with developmental disabilities as compared to their typically developing peers. Research on dietary intake assessment methods in this vulnerable population is lacking. The objectives of this study were to assess the feasibility, acceptability, and compare the nutrient intakes of two technology-based dietary assessment methods in children with-and-without developmental disabilities. This cross-sectional feasibility study was an added aim to a larger pilot study. Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…As children with DS grow older, additional methods may be required to provide adequate dietary data. Technology based methods like image-based mobile food records have been found to be accepted, feasible and promising for nutritional assessment in adolescents with DS (63,64).…”
Section: Nutritional Intakes and Assessmentsmentioning
confidence: 99%
“…As children with DS grow older, additional methods may be required to provide adequate dietary data. Technology based methods like image-based mobile food records have been found to be accepted, feasible and promising for nutritional assessment in adolescents with DS (63,64).…”
Section: Nutritional Intakes and Assessmentsmentioning
confidence: 99%
“…Three articles are presented around the use of web-based methods, which in this special issue were applied in two of three studies to the 24-h recall method [9,10,11]. Interestingly, two studies explored the useability of technology-based methods in populations where use and acceptability might be questioned [9,10]. In one study by Polfuss et al, the usability of a technology-based 24-h recall was explored in individuals with and without disabilities, showing the methods were acceptable [10].…”
Section: Web-based Dietary Assessment Methodsmentioning
confidence: 99%
“…Interestingly, two studies explored the useability of technology-based methods in populations where use and acceptability might be questioned [9,10]. In one study by Polfuss et al, the usability of a technology-based 24-h recall was explored in individuals with and without disabilities, showing the methods were acceptable [10]. Another study in low income adults identified a range of useability issues with the automated self-administered dietary assessment tool (ASA24), including the misunderstanding of questions and uncertainties concerning how to proceed to the next step [9].…”
Section: Web-based Dietary Assessment Methodsmentioning
confidence: 99%
“…A review found that one‐third of such tools used image‐based methods and two‐thirds used integrated databases to estimate energy or nutrient intakes using predominantly self‐reported data ( 30 ) . In addition to mobile apps to assess dietary intake ( 22 ) , technology‐assisted dietary assessment includes web‐based methods in individuals with and without disabilities ( 31 ) and automated electronic methods among low income adults ( 32 ) . Some devices have been proposed to automatically scan and track dietary intake ( 33 ) and analyse food diaries for their nutrient profiles using machine learning algorithms by photographing meals ( 34 ) .…”
Section: Digitally Disrupting Nutrition Assessmentmentioning
confidence: 99%